PERBEDAAN FORMULASI TEH HERBAL DAUN PEPAYA DAN DAUN STEVIA TERHADAP SENYAWA FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN - Gustiani, Karina; Yuliarti, Yuliarti (Indonesian Journal of Nutrition Science and Food, 2022)
Tea is a drink that is familiar inlife everyday. Tea has many health benefits. The phytochemical screening for papaya leaves showed the presence of alkaloids, flavonoids, tannins, and glucosides. Papaya leaves function as antioxidants because they contain flavonoids, vitamin C and vitamin E. Stevia can be used as a natural sweetener that is low in calories because stevia has a sweetness level of 300-400 times sweeter than sucrose. This study used an experimental study design with a completely randomized design (CRD) and repeated four times for each treatment. In the four formulations with 6 assessment components from 100 panelists, namely teachers and employees of SMP Negeri 1 Tanjung Raja and SMP Negeri 1 Sungai Pinang. Organoleptic test of papaya leaf herbal tea and stevia based on the selected formulation was the F1 formulation with 69% color percentage, 61% aroma, and 44% taste. The flavonoid compound test has a positive value which means the presence of flavonoid compounds in papaya leaf herbal teas and stevia leaves. The tannin test has a negative value which means that there is no tannin content in papaya leaf herbal teas and stevia leaves. The antioxidant activity based on the selected formulation is the F1 formulation which has an antioxidant activity of 106.28 ppm. It can be concluded that the F1 formulation is the most preferred formulation and has high antioxidant activity. The antioxidant activity used in this study is IC50, the smaller the ICvalue,50 the higher the concentration of antioxidant compounds that can inhibit free radicals by 50%. It is hoped that further research on quantitative tests of flavonoid compounds in papaya leaf and stevia leaf herbal teas is expected